La identificación humana por medio de la lofoscopia dentro del proceso penal - Medina Sánchez, Jean Carlo (2016)
This work leads to meet in part the need to know and practice proper implementation of different expertise needed for the study and research of different crimes that have gone unpunished, and as future professionals of the branch of law must know, so it exposed my research topic is: “LOPHOSCOPY AS A MEAN OF HUMAN IDENTIFICATION WITHIN A CRIMINAL TRIAL”. In the first part that is in the review of the literature concerning the subject of this investigation, in what is the conceptual framework, I detail on the conceptualization of fingerprinting, fingerprints, crime, and the right of defense. In the doctrinal framework, I present a broad theoretical and doctrinal content specifically related to fingerprinting and different human identification systems. In the legal framework, I refer to constitutional and legal content regarding the proposed theme. Further comprise the results obtained through surveys and interviews own field research, which have been subject to analysis and interpretation of this theme. In the discussion, we proceed to verify the objectives, test the proposal in the draft thesis hypothesis and argue the legal basis to raise legal reforms. Finally to the consideration of the academic authorities and the community in general conclusions, recommendations and proposed legal reform.